The mystery of "metal mouth" in chemotherapy - Reith, AJM; Spence, C (Oxford University Press, 2020)
Of all the oral sensations that are experienced, “metallic” is one that is rarely reported in healthy participants. So why, then, do chemotherapy patients so frequently report that “metallic” sensations overpower and interfere with their enjoyment of food and drink? This side-effect of chemotherapy—often referred to (e.g., by patients) as “metal mouth”—can adversely affect their appetite, resulting in weight loss, which potentially endangers (or at the very least slows) their recovery. The etiology of “metal mouth” is poorly understood, and current management strategies are largely unevidenced. As a result, patients continue to suffer as a result of this poorly understood phenomenon. Here, we provide our perspective on the issue, outlining the evidence for a range of possible etiologies, and highlighting key research questions. We explore the evidence for “metallic” as a putative taste, and whether “metal mouth” might therefore be a form of phantageusia, perhaps similar to already-described “release-of-inhibition” phenomena. We comment on the possibility that “metal mouth” may simply be a direct effect of chemotherapy drugs. We present the novel theory that “metal mouth” may be linked to chemotherapy-induced sensitization of TRPV1. Finally, we discuss the evidence for retronasal olfaction of lipid oxidation products in the etiology of “metal mouth.” This article seeks principally to guide much-needed future research which will hopefully one day provide a basis for the development of novel supportive therapies for future generations of patients undergoing chemotherapy.